Mathematical model for effects of tropical temperature on performance of photovoltaic generators - Ya'acob, Mohammad Effendy (2014)
Based on the presently practised method, Photovoltaic (PV) manufactures estimate the total energy generated from a collection of PV system based on a collection of PV modules datasheet by considering that such data incorporatesthe pertinent percentage of energy conversion capability. The module efficiency estimated in this method does not reflect the collective efficiency of a complete PV generator system. Due to factors such as cost, equipment, space and bulkiness of the system setup, normally a PV generator system cannot be tested in laboratories based on Standard Testing Conditions (STC). Hence the generation capability and the efficiency are solely Mextrapolated by per PV module characteristics. Moreover, the common customer trend for PV system requires more than a single module to be installed at their place.However, related to the issue, there has been little discussion about PV array temperature characteristics especially when it is installed in the tropics. The standard approach of defining the efficiency of a photovoltaic cell strongly depends on the cell temperature, Tc which is calculated using a reference value of the Nominal Operating Cell Temperature (NOCT). Field analysis of a period of ten consecutive months comprising three different PV generator configurations, STC rated at 1 kWp with 12,190 data sets on the 15 minute intervals are the backbone of this work. Rapid fluctuating environmental data flow are the triggering factor to be monitored at site. It consists of both online and ground platform interface via Data Acquisition and Real-Time Monitoring (DART) systemto capture measurement from multiple input sources and analyse in synchronize mode.The crucial part in this study considers dominant influential factors of temperature which are the surface and bottom sides of each PV paneloperated in fluctuating climatic conditions. Based on this issue, to cater for tropical condition, a new condition parameter with a new terminology “tropical Field Operation Cell Temperature (tFOCT)”is introduced. This new condition calculates the PV cell temperature in the tropics with statistical justifications of Generalized Extreme Value Distribution (GEV).Furthermore, by using Multiple Linear Regression (MLR) technique, it is found that the Radiation (G) correlates the PV Power (Ppv) by the factor of 0.76 (in W/m2) andcorrelates with tFOCT by the factor of 25.8 (in 0C). Both factors have significant positive correlationsin enhancing the PV generator output. This study also addresses some findings on the PV array electrical and thermal characteristics comprising five standard operating conditions based on the Sandia National Laboratory (SNL) model. It is found that Fixed Flat (FF) array projects the highest operating value with good regression fit and fairly acceptable correlations. The Tracking Flat (TF) PV Generator is suggested to be the most suitable PVneratorbased on the field performance analysis witha system efficiency of 10.78%. The research contribution lies on the proposed tFOCT condition parameter, array temperature difference (ΔT), array temperaturemodels (Tarray), array electrical/ thermal specifications, PV generator field performanceand the Ppv equation which is brought forward as reference for PV manufacturers and designers who intend to install their PV products in tropical-based countries.